2017
DOI: 10.22146/ifnp.29725
|View full text |Cite
|
Sign up to set email alerts
|

Study of Microbiological Quality and Antioxidant Activity Beras Kencur Drink with Heating Process

Abstract: Beras kencur drink is well known as Indonesian herbal drink made from kencur (Kaempferia galanga L.) mixed with other functional ingredients through minimally-processing. The aim of this research was to evaluate microbiological quality and determine antioxidant activity of beras kencur drink with blanching and pasteurization treatment. Five samples were subjected to microbiological analysis by total plate count (TPC). Furthermore, the variation of heat treatment is blanching (5 and 10 minutes) and pasteurizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…China, Malaysia, Thailand, and Nigeria [19]. Indonesian local people call as "kencur" in Bahasa and mix it with white rice as a beverage or "Jamu Beras Kencur" [20] According to a previous study, the methanol extract of K. galanga increased total antioxidant and ferrous reducing capacities in a concentration-dependent manner. The methanol extract of K.…”
Section: Methodsmentioning
confidence: 99%
“…China, Malaysia, Thailand, and Nigeria [19]. Indonesian local people call as "kencur" in Bahasa and mix it with white rice as a beverage or "Jamu Beras Kencur" [20] According to a previous study, the methanol extract of K. galanga increased total antioxidant and ferrous reducing capacities in a concentration-dependent manner. The methanol extract of K.…”
Section: Methodsmentioning
confidence: 99%
“…Akbar & Murtini (2018), reported that high temperature and heating time have significant changes in the color profile of sugarcane juice drinks. Treatment using heating such as blanching and pasteurization improve the microbiological qualities and antioxidant compound of beras kencur drink, but it can damage the texture and this condition is undesirable (Kiptiyah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%